Freedom of Speech and Freedom of the Press - Arthur L. Goodhart (Washington University Law Quarterly, 1964)
In a famous aphorism Mr. Justice Holmes once said : “[I]t ought always to be remembered that historic continuity with the past is not a duty, it is only a necessity.” In regard to the subject which I am discussing today we can paraphrase this by saying: “In a democracy freedom of speech is not a duty; it is only a necessity.” The essential feature of a democratic system of government is the freedom that is given to the people to choose those who will represent them in carrying on the government of the country, but such a choice would be an empty one unless there were liberty to discuss and to consider those who were being elected. We are all acquainted with the strange elections that are held from time to time in the totalitarian countries; the practical unanimity which is achieved in them is meaningless because no choice is offered.
Keywords: Freedom of speech; Freedom of the press